Innovational tendencies of teaching psychology in technical university - Chugaeva, Nataliya (My University, 2017)
The innovations are always presented by the teachers in the higher educational institutions. Psychology is a science, which is included in all spheres of life and human activity. That`s why, it is studied by students of economic, technological and technical specialities. A few years ago the National University of Food Technologies launched the English-learning project, the integral part of which is teaching the course of "Psychology".
Keywords: психологія; університет; освіта; студенти; англійська мова; psychology; university; education; students; кафедра гуманітарних дисциплін